Characterization of Trileucine Motif in the C-Terminus of the Equine Lutropin/Choriogonadotropin Receptor - Sang-Gwon Kim; Munkhzaya Byambaragchaa; Sei Hyen Park; Ha-Rin Jeong; Jae-Hyek Park; Myung-Hum Park; Myung-Hwa Kang; Kwan-Sik Min (Current Issues in Molecular Biology)
The lutropin/chorionic gonadotropin receptor (LH/CGR) belongs to the G protein-coupled receptor family, characterized by conserved leucine residues in their carboxyl-terminal cytoplasmic tails. This study aimed to investigate the functional significance of the equine LH/CGR (eLH/CGR) trileucine motif in signal transduction. Wild-type eLH/CGR (eLH/CGR-wt) and mutant receptors, in which the trileucine motif was altered to alanine (eLH/CGR-ALL, LAL, LLA, and AAA), were analyzed in transfected cells. The expression levels of mutants ranged from 60% to 78%, with eLH/CGR-AAA showing the lowest level. Although the trileucine motif did not individually affect cAMP responsiveness, the combined mutant (eLH/CGR-AAA) significantly reduced cAMP response, surface receptor levels and enhanced receptor internalization rates. Activation of phospho-ERK1/2 was rapid in all mutants, peaking at 5 min, but eLH/CGR-ALL and LAL mutants exhibited a sharp decline in activity at 15 min. Notably, the eLH/CGR-LLA and AAA mutants showed similar phospho-ERK1/2 activity as the wild type. The eLH/CGR-AAA mutant also displayed a two-fold reduction in PKA signal transduction. These findings suggest that while individual leucine residues of the trileucine motif do not affect cAMP responsiveness, the entire motif plays a crucial role in receptor trafficking and signaling, specifically influencing PKA and phospho-ERK1/2 pathways.